Tipos de injertos en plantas de vivero de cacao nacional (Theobroma cacao L.) - Sandoya Jiménez, Mario José (2019)
The present research work, whose results support the writing of this monograph, was carried out on the grounds of the Will of God nursery. Located in the Zapotal parish of the Ventanas canton. Its objective was to synthesize information on the types of grafts used in cacao cultivation nursery. rafting involves taking a bud from the branch of a tree selected and evaluated, to attach it to a pattern that is a plant generated by seed. This bud, once implanted, is activated and as it grows, it forms the aerial part of the new tree and therefore its genetic characteristics are identical to those of the tree from which the bud was extracted. Before grafting, you should: Disinfect the knife or scalpel with a solution of alcohol or formaldehyde aldehyde (one part of form and five parts of water), clean the site of the pattern where the graft will be performed, using a cotton or a rag moistened with water, the patterns must be under cover at least three days before grafting so that the humidity present in the sheath is minimal and does not cause the formation of a microclimate that will subsequently affect the graft especially in the first days of healing. The types of grafts most used in cocoa are the central or terminal spike, patch grafting, crown grafting and grafting by approximation